Pengaruh Lingkungan Berbahasa Terhadap Ketrampilan Berbahasa Arab - Afifah Azkiyah; Wahyu Hidayat; Dina Indriana (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
This study uses quantitative methods to determine whether the language environment affects one's Arabic speaking ability and how much influence the language environment has on one's Arabic speaking ability. The study collected data through a questionnaire administered to twenty respondents. To measure the relationship between the independent variable-the language environment-and the dependent variable-Arabic speaking skills, simple linear regression data analysis technique was used. The results showed that language environment has a positive and significant effect on Arabic language skills. The regression coefficient value was 0.737. The regression equation found was Y = 4.220 + 0.737X2. The results show that a one unit increase in the language environment will increase Arabic language skills by 0.737 units, with a t-value of 2.486 and a significance level of 0.024, which indicates that the relationship is significant at the 95% confidence level. This conclusion shows that a conducive environment, either through formal learning or informal interaction, can help in the acquisition of Arabic language skills. Therefore, researchers should take steps.